International Conference on Carbon Dioxide Utilisation (ICCDU) 2016 - Peter Styring (Frontiers Research Topics, 2018)
Carbon dioxide utilisation is a growing field of research that spans early stage laboratory chemistry through to commercial exploitation. In 2013 the CO2Chem Network (www.co2chem.com) made a successful bid to hold the 14th edition of this major conference. This was the first time it was held in the United Kingdom and attracted over 270 delegates from 32 different countries. It was a condition of presentation that all the work submitted was new and novel. We invited submissions of new work for this Research Topic and manuscripts were subjected to deep peer review. We are pleased that these papers are now being collated into an eBook. We value the range and quality of the papers submitted. These range from novel capture, integration and process through to policy, public perception and economic evaluation. CO2Chem was proud to be chosen to organise this prestigious conference. CO2Chem was founded in 2010 as one of the Engineering and Physical Sciences (EPSRC) Grand Challenge Networks. It is now in its eighth year of operation and its third round of direct funding. It continues to be a forum for discussion and collaboration nationally and globally. We have for a long time associated ourselves with ICCDU and will continue to do so in the future. We hope that the papers presented here serve as a catalyst to further research in CDU and to engagement with ICCDU.